A meta‐analysis of MitraClip combined with medical therapy vs. medical therapy alone for treatment of mitral regurgitation in heart failure patients. (6th September 2018) - Giannini, Cristina; D'ascenzo, Fabrizio; Fiorelli, Francesca; Spontoni, Paolo; Swaans, Martin J.; Velazquez, Eric J.; Armeni, Patrizio; Adamo, Marianna; De Carlo, Marco; Petronio, Anna Sonia
Abstract: Aims: Survival benefit of percutaneous mitral valve repair with the MitraClip over conservative treatment of functional mitral regurgitation (MR) remains unclear. The purpose of this meta‐analysis is to compare survival outcomes of MitraClip with those of medical therapy in patients with functional MR. Methods and results: A comprehensive literature search of PubMed, MEDLINE, and Google Scholar was conducted including studies evaluating MitraClip vs. medical therapy with multivariate adjustment and with >80% of patients with functional MR. Death from any cause was the primary endpoint, while freedom from readmission was the secondary one, evaluated with random effects. These analyses were performed at study level and at patient level including only functional MR when available, evaluating the effect of MitraClip in different subgroups according to age, ischaemic aetiology, presence of implantable cardioverter defibrillator/cardiac resynchronization therapy, and left ventricular ejection fraction and volumes. We identified six eligible observational studies including 2121 participants who were treated with MitraClip ( n = 833) or conservative therapy ( n = 1288). Clinical follow‐up was documented at a median of 400 days. At study‐level analysis, MitraClip, when compared with medical therapy ( P = 0.005), was associated with significant reduction of death ( P = 0.002) and of readmission due to cardiac disease. At patient‐level analysis, including 344 patients, MitraClip confirmed robust survival benefit over medical therapy for all patients with functional MR and among the most important subgroups. Conclusions: Compared with conservative treatment, MitraClip is associated with a significant survival benefit. Importantly, this superiority is particularly pronounced among patients with functional MR and across all the main subgroups.